ANALYSIS OF COASTLINE CHANGES ON THE POTENTIAL OF MANGROVE FORESTS ON BENGKALIS ISLAND, RIAU PROVINCE - Nabilla, Lulu Mayna; Mubarak, Mubarak; Elizal, Elizal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2021)
This study was conducted from January to February 2021 in coastal areas of Bengkalis Regency that is in Riau Province. This study aims to know the coastline changes to the potency of mangrove forests in that area. Field data was collected by survey methods such as direct observation and questioners, and it used different times of satellite imageries to find out the coastline changes over time. The results showed that the coastline of this regency had changed as much as 1036 Ha in average from the year of 1988 to 2020. It was due to coastal abrasion, wave actions, and reduction of mangrove forests; the coastline change reached 12.02 meters per year as the highest. The mangrove forest in the region of this regency plays important roles to the local life, the local economy, and the coastal waters; it was for fishermen, charcoal production, coastal tourism, and transportation as well.